Pengaruh Design Thinking dan Differentiated Instruction Terhadap Keterampilan Berpikir Kreatif Siswa Kelas VII pada Materi Ekosistem di Sekolah XYZ - Caroline Monica; M.B. Rini Wahyuningsih (Journal on Education, 2024)
Just as the role of Christian teachers in education is to be the agents of reconciliation and transformation, teachers must seek ways to create an appropriate learning environment. This study aims to evaluate the effect of design thinking and differentiated instruction on students' creative thinking. Using the experimental design, data was collected through questionnaires and creative thinking skills tests before and after treatment. The results of the analysis show that the relationship of design thinking to creative thinking skills is not significant with a coefficient of -0.011 on the pretest and -0.149 on the posttest, the relationship of differentiated instruction to creative thinking skills is also not significant with a coefficient of -0.075 on the pretest and -0.127 on the posttest. Together, design thinking and differentiated instruction only explained 0.9% of the variability in creative thinking skills, with an R Square value of 0.009. The ANOVA test showed that this regression model was not significant with an F value of 0.234 and a significance value of 0.792. The conclusion of this study is that design thinking and differentiated instruction have no significant influence on students' creative thinking skills in the sample studied. The findings suggest the need for further exploration.